2011
DOI: 10.4049/jimmunol.1003049
|View full text |Cite
|
Sign up to set email alerts
|

A Brief History of IL-9

Abstract: IL-9 was first described in the late 1980s as a member of a growing number of cytokines that had pleiotropic functions in the immune system. Although many biological functions have been attributed to IL-9, it remains an understudied cytokine. A resurgence of interest in IL-9 has been spurred by recent work demonstrating a role for IL-9 in regulating inflammatory immunity and defining the transcription factors that activate the Il9 gene in cells that most efficiently produce IL-9. In this review, we summarize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
295
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(306 citation statements)
references
References 99 publications
(132 reference statements)
5
295
0
6
Order By: Relevance
“…It has been recently reported that IL-9 transcription in Th9 cells was regulated by the DNA-binding inhibitor Id3 [42]. Although we could not observe IL-9 production by our TILs expanded in vitro whatever the T-cell subpopulation tested (data not shown), IL-9 producing T cells associated with a Th9 phenotype were described in TILs from human melanoma lesions reinforcing the relevance of our data in vivo [43].While a large number of publications described diverse functions of IL-9 acting on a wide spectrum of hematopoietic and nonhematopoietic cell types [39], its effect on human TILs has not been documented yet. Previous studies, largely involving mouse models, have suggested that the common denominator of IL-9 function is to promote the survival of different cell types, including T cells [44] Furthermore, our results indicate that IL-9 treatment maintains, rather than induces, DP T-cell proliferation.…”
supporting
confidence: 44%
See 2 more Smart Citations
“…It has been recently reported that IL-9 transcription in Th9 cells was regulated by the DNA-binding inhibitor Id3 [42]. Although we could not observe IL-9 production by our TILs expanded in vitro whatever the T-cell subpopulation tested (data not shown), IL-9 producing T cells associated with a Th9 phenotype were described in TILs from human melanoma lesions reinforcing the relevance of our data in vivo [43].While a large number of publications described diverse functions of IL-9 acting on a wide spectrum of hematopoietic and nonhematopoietic cell types [39], its effect on human TILs has not been documented yet. Previous studies, largely involving mouse models, have suggested that the common denominator of IL-9 function is to promote the survival of different cell types, including T cells [44] Furthermore, our results indicate that IL-9 treatment maintains, rather than induces, DP T-cell proliferation.…”
supporting
confidence: 44%
“…While a large number of publications described diverse functions of IL-9 acting on a wide spectrum of hematopoietic and nonhematopoietic cell types [39], its effect on human TILs has not been documented yet. Previous studies, largely involving mouse models, have suggested that the common denominator of IL-9 function is to promote the survival of different cell types, including T cells [44], mast cells [35], and eosinophils [45] as well as neurons [46], tumors [47], and epithelial cells [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S2G). Of note, IL-9 and IL-3 promote the proliferation and differentiation of hematopoietic stem cells into myeloid progenitor cells (19,20), and increased systemic levels of IL-9 and IL-3 correlate directly with the myeloid expansion seen in STING/lpr mice ( Fig. 4D).…”
Section: Sting Deficiency But Not Irf3 Deficiency Leads To the Expansmentioning
confidence: 99%
“…IL9 is a pleiotropic cytokine in the T helper cell type 1 (Th1):Th2 pathway. Now, it was well known that a specialized subset termed Th9 cells selectively produce IL9 (Goswami et al, 2011). CDKN2A is a major susceptibility gene for cutaneous malignant melanoma (CMM).…”
Section: Interleukin 10 Rs1800872 T>g Polymorphism Was Associated Witmentioning
confidence: 99%